Content, extraction and export of nutrients in sugarcane under salinity and leaching fraction - Raquele M. de Lira; Ênio F. de F. e Silva; Gerônimo F. da Silva; Diego H. S. de Souza; Elvira M. R. Pedrosa; Leandro C. Gordin (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the contents of macronutrients and also chlorine and sodium in the diagnostic leaf, and the extraction and export of macronutrients in sugarcane irrigated with saline water and leaching fractions. The experiment was conducted in a complete randomized design in a 5 x 2 factorial scheme with four replications, corresponding to five levels of water salinity (0.5, 2.0, 3.5, 5.0 and 6.5 dS m-1) and two leaching fractions (L1 = 0 and L2 = 0.17). The treatments were applied 60 days after planting. At 280 days after planting, diagnostic leaves were collected and used to evaluate the nutritional status and the contents of Cl and Na. At 360 days after planting, the sugarcane was harvested and its stalks were separated into tops and leaves. Exposure to water of increasing salinity linearly reduced the N, P, K and Mg contents of the diagnostic leaves and increased their Ca, Cl and Na contents. This effect was minimized by the application of the 0.17 leaching fraction. The extraction of nutrients followed the order K > Ca > N > Mg > S > P. The salinity of the irrigation water had a negative effect on the nutritional status of the plant and on its extraction and export of nutrients; the application of the 0.17 leaching fraction improved the results, except for Ca and S.